Impact On Affective Commitment Among HRM Professionals in the IT Sector - Amrin, Shaba; Ramyasri, M. D; Jegadeesan, P. (Journal of Neonatal Surgery, 2025)
In today’s competitive and dynamic business environment, fostering employee commitment has become a strategic priority for organizations, especially in the Information Technology (IT) sector, which is characterized by high attrition rates and fast-paced change. This study explores the impact of various organizational and personal factors on affective commitment among Human Resource Management (HRM) professionals within the IT industry. Affective commitment, defined as the emotional attachment of employees to their organization, plays a critical role in influencing job satisfaction, retention, and organizational performance. The study adopts a quantitative research methodology, utilizing a structured questionnaire based on the Meyer and Allen three-component model of commitment. The survey was conducted among 250 HR professionals working in mid-sized and large IT companies in India. Statistical tools such as correlation and regression analysis were used to examine the relationships between affective commitment and factors such as job satisfaction, perceived organizational support, leadership style, career growth opportunities, and work-life balance. Findings indicate that perceived organizational support and job satisfaction have the most significant positive influence on affective commitment. Leadership quality and career advancement opportunities also emerged as strong predictors. Interestingly, work-life balance showed a moderate impact, reflecting the complex nature of HR responsibilities in a 24/7 industry like IT